French Vividness of Olfactory Imagery Questionnaire: A Potential Tool for Diagnosing Olfactory Loss by Assessing Olfactory Imagery? - Fantin, Luca; Ceyte, Hadrien; Ramdane-Cherif, Zhor; Jacquot, Muriel; Hossu, Gabriela (Frontiers in Psychology, 2020)
Several studies have shown a significant relationship between smelling and olfactory imagery abilities. The aim of the present study was to validate a French version of the Vividness of Olfactory Imagery Questionnaire (VOIQ) and to investigate its capability to differentiate populations based on their olfactory ability, and notably those with olfactory loss, which could be of great interest for diagnostic purposes in the current health context. Thanks to a French transaltion of the VOIQ (fVOIQ), we compared olfactory imagery abilities of pathologic (hyposmic and anosmic), normosmic (healthy non-expert) and fragrance expert individual samples. 387 French participants anonymously self-completed the fVOIQ: 121 pathologic individuals, 244 normosmic individuals and 22 fragrance experts. Significant split-half reliability as expressed by Spearman correlation coefficients for the global sample, as well as for each group separately, indicated the excellent internal consistency of the fVOIQ. Moreover, results revealed a significant effect of smelling ability group on fVOIQ score, suggesting that daily olfactory stimulation is fundamental to maintain the ability to create a vivid image and that severe loss of smell may result in progressive impairment of olfactory imagery. The fVOIQ and its original version have similarly high benefit in differentiating individuals based on their olfactory ability, meaning the VOIQ was successfully translated to French. Moreover, it can discriminate individuals with olfactory disorders. We believe that they are relevant tools in the current health context for secure preliminary diagnosis in individuals who are likely to have Covid-19, while respecting social distancing.